A qualitative analysis of adding kindness into the ISBAR handover tool. (12th September 2022) - de Senneville, Lizzie Liew; Brewin, Andrew; Thomas, Alarna; Calvert, Katrina
Abstract : Background: The COVID pandemic has highlighted the stresses experienced by our medical workforce, with worldwide publications attesting to high rates of depression, anxiety and burnout, particularly in junior doctors. Many studies focus on reporting on the prevalence of mental health issues, but not many report on interventional strategies. One of the most stressful interactions in the day of a junior doctor is the medical handover. The incorporation of kindness into clinical handover has coined the term 'KISBAR' to underline the importance of delivering handover in a kind manner. Aim: The aim is to analyse the efficacy of a novel intervention by introducing an emotional support representative to participate in the morning labour ward handover. Methods: We undertook an ethnographic constructivist qualitative research project in a tertiary hospital in Perth, Western Australia, using focus groups to explore the views of junior medical staff on the KISBAR handover tool in the specific context of labour ward handover. Fifty per cent of the total junior doctors from the hospital participated in this study. Results: Four dominant themes arose from analysis of the focus group discussions: (i) inherent stress experienced by junior doctors during the labour ward handover process, (ii) support strategies for junior doctors during labour ward handover; (iii) role modelling and the hidden curriculum aspects of communication from senior doctors at labour ward handover; and (iv) benefit of having an emotional support person present for labour ward handover. Conclusion: Our study confirmed the benefit of having an emotional support person present at labour ward handover: improved perception of safety and an environment that junior doctors found to be supportive. This is a novel and reproducible interventional strategy which is applicable to various obstetric units around Australia.